LIPID METABOLISM OF PAJAJARAN DUCKS FED POMACEA CANALICULATA AND MANIHOT ESCULENTA CRANZT LEAF MEAL IN RATIONS CONTAINING SARDINELLA OIL LEMURU - Laeli Fitrah; Sumiati Sumiati; Rukmiasih Rukmiasih (Asosiasi Dosen Muda Indonesia, 2022)
The purpose of this study was to evaluate the effectiveness of utilizing local feed ingredients, namely Golden Snail (Pomacea Canaliculata) as a source of protein and Cassava Leaf Meal (Manihot Esculenta Cranzt) in rations containing Lemuru Fish Oil (Sardinella Lemuru) against cholesterol reduction and lipid metabolic profile in Pajajaran ducks. This study uses 28-week Pajajaran ducks with an average body weight (bw) of 1648 grams as many as 180 ducks. The diet contains cassava leaf meal and lemuru fish oil with protein 14.26-18.53 energy level 3905-4172 kcal kg-1. The study design used was Factorial 3x2 completely randomized design, with the first factor being the use of cassava leaf meal (0%, 5% 10%) and the second factor being the use of golden snail (0%, 5%). The results showed that the administration of 10% (D10K0) cassava leaf meal was significant (P<0.05) increasing feed consumption by 5.78%, the use of 5% golden snail increased the ration palatability by 5.17%. There was a significant interaction (P<0.05) between cassava leaf and golden snail meal to meat fat and cholesterol consumption, the treatment was able to reduce meat cholesterol level (27.98%). The treatment had no significant effect on blood lipid and egg profiles. The use of 5% golden snail can reduce egg MDA 37.03%, the use of 5% cassava meal decreases MDA eggs by 47.98% while at 10% use cassava leaf meal reduces egg MDA levels by 57.60% and egg fat 2.43%.